Pediatric Behçet's Disease - Yildiz, Mehmet; Haslak, Fatih; Adrovic, Amra; Sahin, Sezgin; Koker, Oya; Barut, Kenan; Kasapcopur, Ozgur (Frontiers in Medicine, 2021)
Behçet’s Disease (BD) is a systemic vasculitis firstly described as a disorder causing aphthous lesion in oral and genital mucosae and uveitis. The disease has an extremely unique distribution characterized by the highest incidence in communities living along the historical Silk road. Although our understanding of the etiopathogenesis of BD has expanded over time, there are still lots of unidentified points in the underlying mechanisms of the disease. The accepted opinion in the light of the current knowledge is that various identified and/or unidentified infectious and/or environmental triggers can take a role as a trigger in individuals with genetic susceptibility. Although the disease usually develops in young adulthood, it is reported that about 15-20% of all Behçet's patients develop in childhood. Pediatric BD differs from adult BD not only with the age of onset but also in the frequency and distribution of clinical findings, disease severity and outcome. While gastrointestinal system involvement, neurological findings, arthralgia and positive family history are more common in children, genital lesions and vascular lesions are more common in adult patients. In addition, a better disease outcome with lower severity score and activity index has been reported in children. The diagnosis of the disease is made according to clinical findings. It can be challenging to diagnose the disease due to the absence of a specific diagnostic test, and the long time interval from the first finding of the disease to the full-blown disease phenotype in pediatric cases. Therefore, many classification criteria have been proposed so far. The widely accepted ones are proposed by the International Study Group. The new sets of classification criteria which is the only one for pediatric BD were also developed for pediatric cases by the PEDBD group. The primary goal for the treatment is preventing the organ damages by suppressing the ongoing inflammation and forestalling the disease flares. The treatment of the BD can be onerous due to its multisystemic nature and a multidisciplinary approach is essential for the management of the patients. In this review article, the definition, clinical findings, epidemiology, etiopathogenesis and treatment will be discussed.